Social and economic policies in Korea : ideas, networks, and linkages - Shin, Dong-Myeon, 1966- (RoutledgeCurzon advances in Korean studies ;, 2003)
A unique explanation of the development of Korean social policy using the concepts of 'policy idea', 'policy network' and 'policy-linkages' to examine the causes, patterns and consequences of state interventions in the economy and social affairs.